Studying of physical development features of elite athletes of combat sports by means of special indexes - Podrigalo, L.; Cynarski, W. J.; Rovnaya, O.; Volodchenko, O.; Halashko, O.; Volodchenko, J. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2019)
Purpose. The analysis of bodybuild features of elite athletes of combat sports with the application of special indexes. Methods. 22 anthropometrical indicators were defined, 13 indexes of physical development were calculated on their basis. 29 elite athletes (Candidates Master of Sports and Masters of Sports) were divided into groups. 1 - 7 athletes (judo, sambo, Greco-Roman wrestling, and freestyle wrestling), (18,43±0,43 years). 2 - 9 kickboxing athletes, (18,22±0,52 years). 3 - 13 combat sports athletes (karate, taekwondo, hand-to-hand fight), (18,00±0,28 years). Results. Higher body mass index in athletes demonstrates the prevalence of muscular component of somatotype. The Erismann and Pignier indexes, shoulders width index illustrate the best development of muscles in athletes and kickboxing athletes in comparison with karate athletes, and taekwondo. Increase in a relative body surface of athletes demonstrates the growth of their aerobic opportunities. Increase in the power index confirms the importance of grip strength for success in combat. Indexes of a ratio of segments of extremities reflect features of the technique of combat sports. Conclusions. The existence of the features caused by combat sports is confirmed. The competency of special indexes application which is especially illustrated ratios of extremities segments in the monitoring of athletes` functional condition is also proved.